Sistem Pengelolaan Limbah Plastik di Kota Lhokseumawe - Provinsi Aceh - Syaifuddin Yana; Dewi Mulyati; Badaruddin Badaruddin; Halimatussakdiah Halimatussakdiah (Fakultas Teknik, 2019)
The study aims to describe the plastic waste management from a processing perspective that has economic value added. Conversion of waste into an economic value, is one practice that can be a role of model, so that it can guide a certain region to do good and correct waste of management. The potential of Aceh’s plastic waste is relatively large, which must be considered by the regional government to be able to realize related to plastic waste processing ctivities by the processor, where the existence is a large potential to be used as an opportunity for recycle. The current practice is still a little and only processing the plastic waste to become plastic chips, and there is no plastic waste processing converted into processed plastic products. The existence of this processing can provide conomic Added value for its owners and provide benefits to local governments as well. Therefore, it is need the role of he Aceh government to bring up the spirit of entrepreneurship, especially in the management and processing of lastic waste. On the other hand, a spirit of togetherness is needed through coordination and cooperation between local governments and non-governmental institutions, activists and environmentalists to carry out the mandate of the law relating to environmental conservation including waste management activities that can be added to conomic value.